2010
DOI: 10.4314/ajtcam.v6i1.57076
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of herbal medicinal products marketed in Kaduna Metropolis with selected pathogenic bacteria.

Abstract: The study aimed to evaluate the bacterial contamination of powdered herbal medicinal preparations sourced from identified herbal retail outlets in different parts of Kaduna metropolis. The assessments of the contamination of the herbal products were carried out using standard procedures: total aerobic bacterial plate count, measurement of some physical parameters, isolation and characterization of selected bacterial pathogens etc. The results showed that out of a total of 150, 70 (46.67%) herbal remedies were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 11 publications
10
64
2
2
Order By: Relevance
“…The limits of bacterial contamination according to the WHO and the European Pharmacopoeia for total aerobic bacteria is 10 7 CFU/g or ml for herbal products to which boiling water is added before use and 10 5 CFU/g or ml for those which boiling water is not added before use (WHO, 2007;EP, 2007). Most of the herbal products (84%) in this study did not meet these specifications and similar findings have been reported (Abba et al, 2008;Okunlola et al, 2007).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The limits of bacterial contamination according to the WHO and the European Pharmacopoeia for total aerobic bacteria is 10 7 CFU/g or ml for herbal products to which boiling water is added before use and 10 5 CFU/g or ml for those which boiling water is not added before use (WHO, 2007;EP, 2007). Most of the herbal products (84%) in this study did not meet these specifications and similar findings have been reported (Abba et al, 2008;Okunlola et al, 2007).…”
Section: Discussionsupporting
confidence: 64%
“…The THPs sampled in this study claimed that they could treat a wide range of illnesses such as malaria, typhoid, amoebiasis, high blood pressure, blood toxins, colon toxins, pneumonia, kidney disease, allergies, heart infections, sexually transmitted diseases, epilepsy, cancer, diabetes, arthritis, sterility, impotence, wound infections, skin infection, urinary tract infections and HIV among others. Abba et al (2008) in their study on herbal products in Kaduma reported that the THPs claim to treat similar diseases and conditions as observed in this study. Although some of the hawkers/street vendors were generous in sharing the knowledge on the plants they use to prepare their products, most of the THPs were not willing to reveal the plants used to prepare their products.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Researchers investigated the microbial load of medicinal plants & spices and found the presence of different contamination including pathogenic bacteria such as Staphylococcus aureus, Shigella spp., Salmonella, Escherichia coli, Clostridium perfringens, fungi, molds, mesophilic aerobic bacteria (total count) and Enterobacteriaceae (36,38,39). In this study, all herbal samples (C. asiatica & Aloe vera) were found to exhibit huge load of total viable bacteria within the range of 10 3 to 10 8 cfu/g as shown in Table 1 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In order to improve the purity and safety of the herb products, monitoring of basic hygiene during preparation and standardization of some physical characteristics such as moisture are desirable (Abba et al, 2009). Drying is the most common and fundamental method for post-harvest preservation of medicinal plants, because it allows for the quick conservation of the medicinal qualities of the plant material in an uncomplicated manner (Rocha et al, 2011).…”
Section: Effect Of Gamma Ray and Electron Beam On Moisture And Ash Comentioning
confidence: 99%